THE RELATIONSHIP BETWEEN SODIUM CONSUMPTION AND BLOOD PRESSURE OF ADOLESCENT GIRLS IN TASIKMALAYA, WEST JAVA - Dian Saraswati; Lilik Hidayanti (International Journal of Health Science & Medical Research, 2023)
The incidence of hypertension in adulthood begins with an increase in blood pressure since adolescence and high blood pressure in adolescents is also associated with an increased risk of Chronic Heart Disease (CHD) as an adult. Consumption of natrium may lead positively associated with an increase in blood pressure in adolescence. The novelty of this study is because it examines the relationship between sodium consumption and blood pressure in adolescent girls. This study aims to analyze the relationship between sodium consumption and blood pressure in adolescent girls in Tasikmalaya, West Java. This research is an observational study with a cross-sectional study design. The population in this study were all female adolescents aged 12-18 years. The independent variables in this study were total sodium consumption, sodium consumption in snacks, sodium consumption in the main menu and sodium contribution from snacks. The natrium intake was measured by non consecutive recall method. The dependent variable was blood pressure measured by sphygmomanometer Omron HEM8712. The data were analyze by Pearson product moment test. The average total sodium consumption is 506.6mg and blood pressure is 113mmH. There was a positive relationship between total daily sodium (p=0.00; r=0.240), sodium in snacks (p=0.002; 0.162), and sodium in daily menus (p=0.001; r-0.182) with  blood pressure. The conclusion natrium intake was correlated with blood pressure in adolescent girls, therefore, they should aware with high sodium food.Keywords : Sodium; Blood pressure; Snacks; Adolescent girls.